Clinical characteristics and outcomes of ST-segment elevation myocardial infarction in a low income setting in rural Bangladesh. (June 2019) - Kim, Dong-Yeon; Wala, Zubin; Islam, Saidul; Islam, Rabiul; Ahn, Mihong
Abstract: Background: In rural areas of Bangladesh, the majority of patients with ST segment elevation myocardial infarction (STEMI) have little access to reperfusion therapy. Even though thrombolysis can be an affordable life-saving treatment in a low income setting, there are few publications in regards to the clinical and socioeconomic features of STEMI with thrombolytic therapy in rural Bangladesh. Method: The information of the patients who were admitted for STEMI between 2010 and 2016 from one rural hospital were collected and reviewed. This audit evaluated clinical outcomes and socioeconomic characteristics of the patients. Result: 164 patients with STEMI were identified in the period and 136 patients (82.93%) underwent thrombolysis. The mean pain-to-door time was 472 min (7.87 h ± 12.40). Only 5.49% of the patients traveled to hospital by ambulances. Overall in-hospital mortality rate and major adverse cardiovascular event (MACE) after STEMI were 19.51% (32/164), 23.17% (38/164), respectively. The need of inotropics (Odds ratio [OR] 16.43, 95% confidence interval [CI] 1.99–135.75, P < 0.01), the use of defibrillation due to ventricular arrhythmias (OR 33.58, 95% CI 2.96–380.49, P < 0.01) were independent predictors of increased in-hospital mortality. Conclusion: In a rural hospital of Bangladesh, in-hospital mortality rate after STEMI is high in spite of thrombolysis and adherence to published guidelines. The prolonged pain-to-door time and the poor coverage of ambulance services in our study highlight the need of community awareness of acute coronary syndrome and comprehensive emergency medical services in rural Bangladesh.